IMPROVING STUDENTS’ TOEFL-LIKE SCORE THROUGH STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Rionaldi Rionaldi; Boni Saputra (Politeknik Negeri Bengkalis, 2019)
TOEFL (Test of English as a Foreign Language) is an internationally-standardized English proficiency test that is widely used in Indonesia for scholarship selection purposes, graduation and recruitment requirements and placements for English language schools. However, many students, especially D3 English Study Program, State Polytechnic of Bengkalis students still faced difficulties in achieving TOEFL score required. This paper tries to propose Student Team Achievement Division (STAD to improve students’ TOEFL-Like score. It is a five interlocking components: class presentations, teams, quizzes, individual improvement scoring, and team recognition. The research was conducted in two cycles. The results found that STAD increases students’ TOEFL-like scores. The average score of students’ TOEFL-like score before applying STAD was 372. At the cycle 1, there was a slight increase to be 401,9. Then, at the end of the cycle 2, it increased to be 457.73. It means that STAD was effective in improving students’ TOEFL-like score. Therefore, it is suggested to be beneficial strategies applied in teaching and learning TOEFL to improve students’ TOEFL scores.